2020
DOI: 10.34172/aim.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

The First Inherited Retinal Disease Registry in Iran: Research Protocol and Results of a Pilot Study

Abstract: Background: To describe the protocol for developing a national inherited retinal disease (IRD) registry in Iran and present its initial report. Methods: This community-based participatory research was approved by the Ministry of Health and Medical Education of Iran in 2016. To provide the minimum data set (MDS), several focus group meetings were held. The final MDS was handed over to an engineering team to develop a web-based software. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Macular dystrophy with flecks was the second most common IRD category, suggesting ABCA4 retinopathy as the most common macular IRD diagnosis. The distribution of IRD phenotypes in our cohort is similar to those reported in Spain, 26 , 27 the US, 14 , 28 the UK, 29 Iran, 30 and Norway. 31 The Australian Inherited Retinal Disease Registry and DNA Bank also reported that retinitis pigmentosa and Stargardt disease are the most common two diagnoses among over 9000 Australian patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Macular dystrophy with flecks was the second most common IRD category, suggesting ABCA4 retinopathy as the most common macular IRD diagnosis. The distribution of IRD phenotypes in our cohort is similar to those reported in Spain, 26 , 27 the US, 14 , 28 the UK, 29 Iran, 30 and Norway. 31 The Australian Inherited Retinal Disease Registry and DNA Bank also reported that retinitis pigmentosa and Stargardt disease are the most common two diagnoses among over 9000 Australian patients.…”
Section: Discussionsupporting
confidence: 87%
“…However, our results are less than those reported in Brazil (>10%), 35 Spain (11%), 22 and Iran (76%). 30 A study by Khan et al (2017) found that diagnostic yield increased from 45% to 60% when consanguinity was considered to select the most appropriate test. 36 This result supports the importance of capturing patients’ ethnic background and pedigree structure to increase detection rates of the disease-causing variant.…”
Section: Discussionmentioning
confidence: 99%
“…Some countries are actively tackling the issue of integrating genetic services into future planning for their healthcare systems. Portugal and Iran are two of the latest countries to announce the launch of their nationwide registries for IRDs [ 174 , 175 ]. These registries aim to increase accessibility for individuals, while also providing a comprehensive dataset for investigators and clinicians to boost and develop their research.…”
Section: Impacts On Ird Diagnosis Outside Of Ngs Testingmentioning
confidence: 99%
“…None of the probands reportedly suffered from intellectual disability. Fifty-two Iranian index patients from consanguineous families were seen by ophthalmologists in different centers and were cataloged in the Iranian Inherited Retinal Disease Registry (NCT04131400) (Sabbaghi et al 2020). Seven non-consanguineous Mexican probands were recruited by medical geneticists in the Asociación Para Evitar la Ceguera en México (APEC) and the National Institute of Rehabilitation (INR), Mexico City.…”
Section: Patientsmentioning
confidence: 99%